2020
DOI: 10.1111/iju.14307
|View full text |Cite
|
Sign up to set email alerts
|

Obese men undergoing radical prostatectomy: Is robotic or retropubic better to limit positive surgical margins? Results from SEARCH

Abstract: Objectives: To evaluate the association between obesity and positive surgical margins in patients undergoing retropubic radical prostatectomy versus robotic-assisted laparoscopic prostatectomy. Methods: We retrospectively reviewed the data of 3141 men undergoing retropubic radical prostatectomy and 1625 undergoing robotic-assisted laparoscopic prostatectomy between 1988 and 2017 at eight Veterans Health Administration hospitals. The positive surgical margin location (peripheral, apical, bladder neck, overall) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A total of 14 articles regarding obesity and postoperative recurrence and prognosis were included (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). As shown in Figure 2, a significant heterogeneity among the studies was identified (I 2 =71.0%, P=0.000), so the REM was used.…”
Section: Comparison Of Postoperative Recurrence and Prognosis In Obese And Non-obese Pca Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 14 articles regarding obesity and postoperative recurrence and prognosis were included (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). As shown in Figure 2, a significant heterogeneity among the studies was identified (I 2 =71.0%, P=0.000), so the REM was used.…”
Section: Comparison Of Postoperative Recurrence and Prognosis In Obese And Non-obese Pca Patientsmentioning
confidence: 99%
“…A total of five articles were included to report the PSM condition of patients (12)(13)(14)17,21). Firstly, obvious heterogeneity was identified among the studies (I 2 =50.9%, P<0.001) (Figure 6A), so the REM was used for meta-analysis.…”
Section: Psm Conditions In Obese and Non-obese Pca Patients After Surgerymentioning
confidence: 99%
“…A 2020 multicenter retrospective cohort study by Nik‐Ahd et al 27 investigated the association between obesity and positive surgical margins (PSMs) in patients undergoing RALP versus retropubic RP (RRP). The study found that at all locations except the bladder neck, higher BMI was associated with increased odds of overall, peripheral, and apical PSMs among all patients.…”
Section: Risks Of Robotic Pelvic Surgery In Obese Patientsmentioning
confidence: 99%
“…Higher BMI is a risk factor for PSMs, and the association between obesity and PSMs is slightly stronger for men undergoing RRP than for those undergoing RALP. 27 …”
Section: Risks Of Robotic Pelvic Surgery In Obese Patientsmentioning
confidence: 99%
“…The optimal outcome for clinically localized prostate cancer is freedom from the pentafecta: (i) biochemical recurrence; (ii) recovery of continence; (iii) recovery of erectile function; (iv) no perioperative complications; and (v) the absence of positive surgical margins 1 . In the present article, Nik‐Ahd et al retrospectively investigated the SEARCH database, so they could stratify patients with localized prostate cancer according to body mass index (BMI) category who underwent retropubic radical prostatectomy versus robot‐assisted laparoscopic prostatectomy 2 . As expected, higher BMI was associated with a higher rate of whole positive surgical margins (PSMs).…”
mentioning
confidence: 98%